5 ways to boost your business through influencer marketing - LUI, Patricia (Institutional Knowledge at Singapore Management University, 2020)
Covid-19 pandemic’s economic impact put pressure on marketing budgets. Brands are more careful when deciding how they spend the funds on digital marketing, including influencer strategy. The blog offers tips on how to tap on influencers to create brand awareness and generate business leads and conversions.